Conjugate Gradient Method for System of Linear Algebraic Equations - Salah Gazi Shareef , Diman Abdulqader Sulaiman (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Conjugate Gradient Method is an iterative technique for solving large sparse systems of linear equations. As a linear algebra and matrix manipulation technique, it is a useful tool in approximating solutions to linearized partial differential equations. The fundamental concepts are introduced and utilized as the foundation for the derivation of the Conjugate Gradient Method